Political Connectedness, Corporate Governance, and Firm Performance - Domadenik, Polona (Journal of business ethics, 2016)
In this paper, we present and test a theory of how political connectedness (often linked to political corruption) affects corporate governance and productive efficiency of firms. Our model predicts that underdeveloped democratic institutions that do not punish political corruption result in political connectedness of firms that in turn has a negative effect on performance. We test this prediction on an almost complete population of Slovenian joint-stock companies with 100 or more employees. Using the data on supervisory board structure, together with balance sheet and income statement data for 2000–2010, we show that a higher share of politically connected supervisory board members leads to lower productivity.